Financial Performance of ESG-Classified Sustainable Mutual Funds: Evidence from Developing Countries during the COVID-19 Period - Zamani, Kishwar; Jawa, Rachna; Singh, Sumanjeet; Kumar, Vimal; Paliwal, Minakshi; Raj, Rohit; Kumari, Nidhi (Asian Journal of Interdisciplinary Research, 2026)
This study presents a comparative evaluation of ESG-classified sustainable mutual funds and matched conventional mutual funds across eight developing countries. The analysis uses monthly net asset value (NAV) data from Bloomberg, Treasury-bill data from central-bank sources, and Carhart four-factor values from Kenneth R. French’s data library. The sample is restricted to active equity funds with at least six months of available observations; therefore, the findings should be interpreted in light of possible survivorship bias and uneven country-level sample sizes. Rather than directly measuring portfolio-company ESG scores, the study identifies sustainable funds through ESG product classification and compares them with two age-matched conventional funds for each ESG fund. Using raw return comparisons, CAPM alpha, Sharpe ratio, eSDAR, and Carhart’s four-factor model, the study finds no uniform performance premium or penalty for ESG-classified funds across developing markets. The relative difference portfolios generally do not show statistically significant alphas after controlling for market, size, value, and momentum factors, although some ESG portfolios display significant absolute abnormal returns against their national benchmarks. During the COVID-19 period from March 2020 to February 2022, ESG-classified funds in China, Indonesia, and South Africa performed more favourably than their matched conventional peers, while Brazil and Thailand showed weaker market-adjusted performance. The results, therefore, support a country-specific and cautious interpretation: ESG classification may be associated with resilience in some developing markets, but it should not be treated as evidence of a general ESG performance advantage.